2022
DOI: 10.3389/fcell.2021.792185
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs and Brain Tumors: Insights Into Their Roles in Apoptosis

Abstract: A major terrifying ailment afflicting the humans throughout the world is brain tumor, which causes a lot of mortality among pediatric and adult solid tumors. Several major barriers to the treatment and diagnosis of the brain tumors are the specific micro-environmental and cell-intrinsic features of neural tissues. Absence of the nutrients and hypoxia trigger the cells’ mortality in the core of the tumors of humans’ brains: however, type of the cells’ mortality, including apoptosis or necrosis, has been not fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 149 publications
0
12
0
Order By: Relevance
“…An individual miRNA may affect the expression of several mRNAs, while several miRNAs could control each mRNA ( Chen et al, 2021a ; Raue et al, 2021 ). MiRNAs perform a vital role in controlling cell proliferation, apoptosis, migration, and differentiation by modulating the expression of their target genes ( Tamtaji et al, 2021 ). Dysregulated miRNA expression is linked with tumor growth, progression, and chemoresistance in many cancers ( Tu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…An individual miRNA may affect the expression of several mRNAs, while several miRNAs could control each mRNA ( Chen et al, 2021a ; Raue et al, 2021 ). MiRNAs perform a vital role in controlling cell proliferation, apoptosis, migration, and differentiation by modulating the expression of their target genes ( Tamtaji et al, 2021 ). Dysregulated miRNA expression is linked with tumor growth, progression, and chemoresistance in many cancers ( Tu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs act as key regulators of a wide variety of cellular mechanisms and physiological processes, such as cell cycle progression, cell division, apoptosis and necroptosis (62,62,(94)(95)(96)(97)(98)(99)(100)(101)(102). Recent studies have demonstrated that numerous miRNAs can strongly affect the expression of pro-and antiapoptotic genes, oncogenes, ER stress-and/or necroptosisrelated genes (20,103). Aberrations involving miRNAs implicated in apoptosis or necroptosis could also impact physiological conditions and promote disease, including carcinogenesis and infection diseases (19,(104)(105)(106).…”
Section: N2bmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) are transcripts that do not code for proteins, which can be roughly divided into small non-coding RNAs (smaller than 200 nt) and long non-coding RNAs (lncRNAs, longer than 200 nt) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). NcRNAs account for the majority of transcriptome, interestingly the amount of ncRNAs correlates with organismal complexity (26).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs are transcripts with a length of ≥200 nucleotides (nt) [ 4 ]. LncRNAs, like messenger RNAs (mRNAs), are transcribed by RNA polymerase II or III, spliced and capped at 5′ ends [ 5 ]. Contrary to mRNAs, lncRNAs are expressed at low levels and in highly spatiotemporal patterns, generally showing poor conservation across species [ 6 ].…”
Section: Introductionmentioning
confidence: 99%